Research on Pathways to Desistance (Maricopa County, AZ and Philadelphia County, PA): Release Measures - Scales, 2000-2010 (Restricted) - Mulvey, Edward P. ([Verlag nicht ermittelbar], 2017)
The Pathways to Desistance study was a multi-site study that followed 1,354 serious juvenile offenders from adolescence to young adulthood in two locales between the years 2000 and 2010. Enrolled into the study were adjudicated youths from the juvenile and adult court systems in Maricopa County (Phoenix), Arizona (N=654) and Philadelphia County, Pennsylvania (N=700). The Release data portion of the Pathways study contains information from 1,130 interviews ("release interviews") reflecting the youths' perceptions regarding various aspects of the residential experience and institutional environment (e.g., accounts of program operations and services provided, ratings regarding the participant's feelings of his or her safety in the facility). The release interview was conducted within 30 days prior to or after release from a facility and in a separate session apart from the time point interview. This was done to minimize the burden on the research participant and to ensure adequate attention to institutional ratings. The restricted time period within which to conduct the release interview reduced the likelihood that intervening events and experiences would skew the participant's recall of the stay. Study participants could contribute more than one release interview, depending upon the number of institutional placements he/she had over the seven-year follow-up period. The current release data reflects ratings from 686 unique individuals. It should be recognized that not every institutional stay for every youth produced a release interview. On the basis of the number of reported institutional stays in the sample, it is estimated that a release interview was obtained for approximately 54 percent of the total number of residential stays experienced by study participants. Release interviews were missed if the research interviewer was not aware of the institutional stay (e.g. it occurred between time point interviews) or if the interviewer only became aware of the institutional stay at a point that was too late to schedule a release interview within the required window surrounding the release date. The 686 individuals reflected in the release data represent 51 percent of the Pathway study participants (n=1,354) and 56 percent of Pathways participants who had a least one institutional stay (n=1,234; 120 Pathways youths had no institutional stays). On average, these 686 youths had 1.6 interviews. The number of interviews per unique person ranges from one to eight. The current Release Measures study primarily consists of the calculated scores from constructs asked about during the interviews, but the individual scale items were withheld at that time. This study contains those individual items plus the calculated scores.